1982
DOI: 10.1080/01652176.1982.9693850
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with a homologous, inactivated canine parvovirus vaccine in vaccination programmes for dogs

Abstract: The significance of canine parvovirus (CPV) infections as a permanent threat susceptible dogs, in particular pups, made the authors develop three liquid homologous inactivated adjuvant CPV vaccines that were compatible with existing canine vaccines and could be incorporated in current vaccination programmes. On vaccine (Kavak Parvo) contained only the CPV component, the second product (Kavak i-LP) also contained two inactivated leptospiral antigens, and the third vaccine (Kavak i-HLP) contained in addition an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Because inactivated vaccines induce predominantly humoral responses and inactivated vaccines against canine (CPV), feline (FPV), mink (MEV), and porcine (PPV) parvoviruses are highly effective, antibodies are generally thought to constitute an important protective mechanism against parvoviral infection (36,39,41,43). However, it has been reported that under special circumstances, such as in animals surviving intrauterine infection, PPV can persist despite high levels of antiviral antibodies (12).…”
Section: Discussionmentioning
confidence: 97%
“…Because inactivated vaccines induce predominantly humoral responses and inactivated vaccines against canine (CPV), feline (FPV), mink (MEV), and porcine (PPV) parvoviruses are highly effective, antibodies are generally thought to constitute an important protective mechanism against parvoviral infection (36,39,41,43). However, it has been reported that under special circumstances, such as in animals surviving intrauterine infection, PPV can persist despite high levels of antiviral antibodies (12).…”
Section: Discussionmentioning
confidence: 97%
“…It was observed that the baseline sera had some anti-Parvo virus IgG. This could be due to maternal antibody transfer that was sustained in the puppies while we collected samples [29]. Findings of the current study also suggest that the dogs received single or double dose of parvo virus vaccine induced IgG generation, indicating the presence of IgG-inducible parvo virus antigen in the vaccine Nobivac Dog® that were maintained proper cool chain during transportation from lab to dog.…”
Section: Discussionmentioning
confidence: 50%
“…Both groups had mean PLT within the reference range (Table 3). The significant decrease (P<0.03) in PLT for the severely leukopenic group in M2-3 can be attributed to decreased bone marrow production and/or increased consumption/ destruction (Wilson and Hermann-Dekkers, 1982).…”
Section: Arqmentioning
confidence: 94%